In vivo biometry and carcass characteristics of lambs in different finishing systems - Juliano Henriques da Motta (Semina: Ciências Agrárias, 2019)
The aim of this study was to assess the influence of different finishing systems on the in vivo measurements, quantitative and qualitative carcass characteristics, commercial cut ratio, and shoulder tissue composition of lambs. Thirty-two male lambs were distributed in four finishing systems with eight replications each, as follows: suckling lambs on pasture; suckling lambs in confinement, with access to creep-feeding containing corn bran and soybean meal; weaned lambs fed roughage, characterized by ad libitum supply of alfalfa hay; and weaned lambs fed concentrate, composed of oat grain and soybean meal. The lambs were slaughtered as they reached the pre-set live weight at slaughtering of 30 kg. Most of the in vivo biometry variables were not significant (P > 0.05) when comparing the finishing systems, except for hindlimb height and thoracic perimeter. Regarding the quantitative carcass characteristics, all variables differed (P < 0.05) between systems, except for carcass length, leg width, and subcutaneous fat thickness. For the qualitative carcass characteristics, only the fatness and carcass conformation presented significant differences (P < 0.05). Most in vivo measurements and the proportion of carcass cuts were not influenced by finishing systems. Weaned lambs fed an exclusive concentrate diet presented leaner carcasses with an inferior conformation when compared to the other finishing systems. Suckling lambs in confinement presented shoulders with a higher fat deposition when compared to those weaned. Suckling lambs both on pasture and in confinement presented a superiority in the quantitative carcass characteristics when compared to weaned lambs.